Switched beam antenna array with parasitic elements - Kamarudin, Muhammad Ramlee (Electromagnetics Academy, 2009)
This paper describes the design of the disk-loaded monopole with a parasitic array for beam switching. Usually the radiation pattern of a single element such as a ?/4 monopole and the disk-loaded monopole provide low values of gain. The beamwidth is normally large and the coverage is wide. This may be appropriate in an on-body channel where the antenna orientation may not be easily controlled, such as when the users put the terminal in their pocket. In some non-body applications such as WLAN, it is necessary to design antennas with high gain to meet other demands such as high capacity or long range. Also, in the on-body environment it is essential to have such gain in order to minimize the path loss between the antennas, and hence increase the battery life. The antenna was excited using coaxial cable produced more gain and pattern compared to the single element top disk-loaded antenna. The reduced-size antenna namely a sector antenna array also has been discussed in detail in this paper. Such design has allowed at least 50% of the size reduction. The simulation results have shown very good agreement with the measurement for both antennas.